2021
DOI: 10.1002/mame.202100255
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance and Biobased Polyamide/Functionalized Graphene Oxide Nanocomposites through In Situ Polymerization for Engineering Applications

Abstract: In this study, biobased polyamide/functionalized graphene oxide (PA‐FGO) nanocomposite is developed using sustainable resources. Renewable PA is synthesized via polycondensation of hexamethylenediamine (HMDA) and biobased tetradecanedioic acid. Furthermore, GO is functionalized with HMDA to improve its compatibility with biobased PA and in situ polymerization is employed to obtain homogeneous PA‐FGO nanocomposites. Compatibility improvement provides simultaneous increases in the tensile strength, storage modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Biobased PA GO (functionalized with hexamethylenediamine) In situ polymerization [359] PLA/PCL Thermally exfoliated reduced graphene oxide (f-TERGO)…”
Section: Cbmentioning
confidence: 99%
“…Biobased PA GO (functionalized with hexamethylenediamine) In situ polymerization [359] PLA/PCL Thermally exfoliated reduced graphene oxide (f-TERGO)…”
Section: Cbmentioning
confidence: 99%
“…Lignin displayed three distinct weight loss regions; the first one appeared below 200 • C, corresponding mainly to water release; the second one between 200 and 550 • C with a broad DTG peak at 320 • C assigned for major devolatilization reactions; and finally, a minor weight loss above 550 • C attributed to the decomposition of the most thermally stable organic matter [33]. The thermal decomposition stages were repeated for the surface-modified lignin particles; in addition, one new weight loss region appeared between 200 and 300 • C, accompanied by a DTG peak at 270 • C. It has been shown that most of the aliphatic molecules thermally decompose in the range of 200-300 • C [10]; therefore, the appearance of this peak could be associated with the decomposition of ODI molecules attached to lignin particles. It is worth noting that the maximum thermal degradation of lignin shifted towards a higher temperature, from 320 • to 345 • C, in the surface-modified sample, which has been attributed to the increase in the crystallinity of the sample after surface modification [34,35].…”
Section: Lignin Particles Surface Modificationmentioning
confidence: 99%
“…As one of the most promising vegetable oils, castor oil has been extensively used to develop partially and fully bio-based sustainable polymers, including polyurethanes, polyesters, and polyamides [6,7]. Polyamides, PAs, also known as nylons, are polymer families with high-performance properties, including superior mechanical strength, high stiffness/toughness, good thermal stability, and excellent resistance to a wide range of organic and inorganic solvents [8][9][10]. Polyamides are recyclable and, fortunately, can be synthesized from renewable biomass resources, such as castor oil.…”
Section: Introductionmentioning
confidence: 99%
“…These results are promising for the design of durable, biosensors or real-time monitorization of patient-adapted wearable devices. [27] GO has also shown good biocompatibility with fibroblast cells [28] and possess bactericidal properties via oxidative stress, [29] making it an excellent candidate for tissue engineering applications, [30] bio-based materials for high performance scaffolds, [31] or stimuli-responsive materials for drug delivery. [32] In this work, we present a series of nanocomposites manufactured via SL where GO is used both as a reinforcing agent and as a smart platform for material functionalization through simple surface modification reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These results are promising for the design of durable, biosensors or real‐time monitorization of patient‐adapted wearable devices. [ 27 ] GO has also shown good biocompatibility with fibroblast cells [ 28 ] and possess bactericidal properties via oxidative stress, [ 29 ] making it an excellent candidate for tissue engineering applications, [ 30 ] bio‐based materials for high performance scaffolds, [ 31 ] or stimuli‐responsive materials for drug delivery. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%